2018
DOI: 10.3390/agronomy8110257
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Water and Nitrogen Availability on the Expression of End-Use Quality Parameters of Spring Wheat

Abstract: Wheat (Triticum aestivum L.) grain quality is determined by multiple physical and chemical attributes. However, previous studies mainly focused on protein quantity and composition, which may not be adequate for understanding grain quality, especially end-use quality. Field experiments were conducted at two locations for two years to better understand how and to what extent water and nitrogen (N) availability affect flour end-use quality. Four drought stress levels (i.e., mild, moderate, severe, and well-watere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
5
18
2
Order By: Relevance
“…When data were pooled over N rates, the means comparison using the Orthogonal Polynomial Contrasts (Table 5) revealed that wheat yield was not statistically different between medium and high IR treatments. This agrees with the recent deficit IR studies in Idaho and Montana (Torrion & Stougaard, 2017;Yang et al, 2018).…”
Section: Grain Yield and Yield Componentssupporting
confidence: 93%
“…When data were pooled over N rates, the means comparison using the Orthogonal Polynomial Contrasts (Table 5) revealed that wheat yield was not statistically different between medium and high IR treatments. This agrees with the recent deficit IR studies in Idaho and Montana (Torrion & Stougaard, 2017;Yang et al, 2018).…”
Section: Grain Yield and Yield Componentssupporting
confidence: 93%
“…The results of our study confirm that even if wheat grain yields are not always increased with N applications, N fertilizer could still be beneficial in terms of improved grain quality (grain test weight and grain protein content). This agrees with findings by Yang et al (2018), reporting that although wheat grain yield did not respond to N fertilization, wheat quality parameters (including flower protein content) were positively influenced by N application in all wheat cultivars assessed in that study.…”
Section: Biomass Productionsupporting
confidence: 93%
“…Our results in grain yield and protein in response to N supplies were consistent with the findings of Yang et al [34] and Klikocka et al [35]. Webster and Jackson [30] found that N top-dressing at anthesis increased grain protein content by 1.6 to 7.4% depending on N rate and soil residual N before anthesis.…”
Section: Yield and Protein Contentsupporting
confidence: 92%